Bulk Resistance and Contact Impedance: Particular Solution for Annulus, Homogeneous Domain and Dimensional Analysis of the Complete Electrode Model - Sepulveda-Palma, F (Elsevier B.V., 2024)
Viewing the complexity of multiphase flows, in which multi-dimensional and time-changing fluid structures, known as flow patterns, must be captured, electrical impedance tomography (EIT) stands out as an alternative for fluid flow visualization. Using an EIT system, this study presents an enhanced approach for measuring film thickness in two-phase flows. Incorporating bulk resistance and contact impedance contributions, the proposed ohmic model significantly improves accuracy, particularly in low-conductivity scenarios, yielding a robust, accurate, and rapid technique for obtaining images from an EIT-based low-cost acquisition system. Tomographic experiments validate the model s efficacy using cylindrical sensors and diverse conductivity mediums, including two distinct phantoms. The dimensional analysis of the model yields five dimensionless numbers, revealing interrelations between electrical parameters and sensor construction. A correlation based on a dimensionless number for the contact impedance is obtained. Additionally, the experiments demonstrate a strong interplay with the polarization phenomenon. © 2024 Elsevier Ltd